2017
DOI: 10.1016/j.rboe.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Open versus arthroscopic approach in the treatment of femoroacetabular impingement: a case–control study with two-years follow up

Abstract: ObjectiveTo compare clinical and imaging results and complications between patients treated for femoroacetabular impingement (FAI) who underwent either anterior open surgery or an arthroscopic approach, with a minimum follow-up of two years.MethodsThis retrospective case–control study included patients submitted to FAI surgical treatment between November 2007 and March 2012. Patients treated with open surgery were compared with those treated with arthroscopy. Patients were clinically assessed by the modified H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…[ 174 ] 2018 III Portugal Retrospective 59 y 198 NAHS 1 56 INCLUDING BOTH Ribas, M. [ 176 ] 2007 IV Spain Retrospective 29.2 y 32 The Merle d’Aubigné -Postel score, WOMAC 2 72 MINI-OPEN TECHNIQUE Riff, A. J. [ 177 ] 2018 IV USA Retrospective 24 y 32 HOS (ADL + SS), mHHS, VAS pain, VAS satisfaction 2 40 ARTHROSCOPIC Rivera, E. [ 178 ] 2020 III Spain Retrospective 24 n 80 iHOT-33, mHHS, VAS pain 2 66 ARTHROSCOPIC Roos, B. D. [ 179 ] 2017 III Brazil Retrospective 36 a n 56 mHHS, NAHS 2 84 INCLUDING BOTH …”
Section: Resultsmentioning
confidence: 99%
“…[ 174 ] 2018 III Portugal Retrospective 59 y 198 NAHS 1 56 INCLUDING BOTH Ribas, M. [ 176 ] 2007 IV Spain Retrospective 29.2 y 32 The Merle d’Aubigné -Postel score, WOMAC 2 72 MINI-OPEN TECHNIQUE Riff, A. J. [ 177 ] 2018 IV USA Retrospective 24 y 32 HOS (ADL + SS), mHHS, VAS pain, VAS satisfaction 2 40 ARTHROSCOPIC Rivera, E. [ 178 ] 2020 III Spain Retrospective 24 n 80 iHOT-33, mHHS, VAS pain 2 66 ARTHROSCOPIC Roos, B. D. [ 179 ] 2017 III Brazil Retrospective 36 a n 56 mHHS, NAHS 2 84 INCLUDING BOTH …”
Section: Resultsmentioning
confidence: 99%
“…Comparison of postoperative mHHS between AT and OT was conducted among the 3 included studies, [ 14 , 16 , 17 ] which included 124 patients (83 patients receiving AT and 41 patients receiving OT), as shown in Figure 2 . Heterogeneity testing showed that there was low heterogeneity among the studies ( P = .33, I 2 = 9%), so the fixed-effect model was used to pool the data from the 3 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of postoperative satisfaction rate between AT and OT was conducted among 2 included studies [ 14 , 16 ] which contain 86 patients in Figure 4 . A heterogeneity test showed that there was no heterogeneity among studies ( P = .71, I 2 = 0%), so the fixed-effect model was used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations